Using the natural polymer chitosan in harvesting cenedesmus species under different concentrations and Cultural ph values - IBRAHIM A. MATTER; OSAMA M. DARWESH; FAROUK K. EL-BAZ (International Journal of Pharma and Bio Sciences, 2016)
Harvesting of microalgae Scenedesmus sp. (strain A1) using the natural polymer chitosan was investigated. Different chitosan concentrations, i.e., 10, 20, 40, 60 and 80 ppm were used in the pH range 6 to 10 and cultural cell densities values equivalent to 1, 2 and 3 abs680. Without the addition of chitosan, the increase in pH of the culture led to limited cell sedimentation. The addition of chitosan to the cultures at concentrations ranged from 10 to 80 ppm caused bio-flocculation followed by noticeable sedimentation of the trailed microalgae. The harvesting efficiency of Scenedesmus sp. using chitosan is very sensitive to the pH of the algal culture and pH 7 and 8 were the most suitable ones. In culture with OD680=1, 80 ppm chitosan is able to achieve 74% flocculation efficiency at pH 8, while 40 ppm chitosan caused 60.1% flocculation when pH value adjusted at 7. It could be concluded that, the cultural cell density determines the optimal chitosan dosage required for flocculation, the highest sedimentation percentage using 40 ppm chitosan could be achieved under pH 7 and OD3 (82.1%). In addition, in acidic and neutral cultures, the flocculation efficiency (FE) tends to be higher in case of dense cultures.